Synthetic sutures: clinical evaluation and future developments - Abhari, R; Martins, J; Morris, H; Mouthuy, P; Carr, A (SAGE Publications, 2017)
Today's sutures are the result of a 4000-year innovation process with regard to their materials and manufacturing techniques, yet little has been done to enhance the therapeutic value of the suture itself. In this review, we explore the historical development, regulatory database and clinical literature of sutures to gain a fuller picture of suture advances to date. First, we examine historical shifts in suture manufacturing companies and review suture regulatory databases to understand the forces driving suture development. Second, we gather the existing clinical evidence of suture efficacy from reviewing the clinical literature and the Food and Drug Administration database in order to identify to what extent sutures have been clinically evaluated and the key clinical areas that would benefit from improved suture materials. Finally, we apply tissue engineering and regenerative medicine design hypotheses to suture materials to identify routes by which bioactive sutures can be designed and passed through regulatory hurdles, to improve surgical outcomes. Our review of the clinical literature revealed that many of the sutures currently in use have been available for decades, yet have never been clinically evaluated. Since suture design and development is industry driven, incremental modifications have allowed for a steady outflow of products while maintaining a safe regulatory position and limiting costs. Until recently, there has been little academic interest in suture development, however the rise of regenerative medicine strategies is shifting the suture paradigm from an inert material, which mechanically approximates tissue, to a bioactive material, which also actively promotes cell-directed repair and a positive healing response. These materials hold significant therapeutic potential, but could be associated with an increased regulatory burden, cost, and clinical evaluation compared with current devices.